A comprehensive survey of pre-authentication approach towards proxy re-encryption in cloud data context - Singh, Amish; Shukla, Saurabh; B, Sowmiya (International Journal of Engineering and Technology, 2018)
This survey paper categorizes, compares, andsummarizes the algorithms, data sets and performance measurement in the published articles related to proxy re-encryption and medical systems. Most of the systems either deploy a pre-authentication approach or a proxy re-encryption approach, they are seldom seen together. Most of the systems either take a patient -centric or a doctor-centric approach whereas the demand is for a common system that can be accessible to all access groups. Multi-data sharing is another concept that is necessary to be implemented in the newer systems and is lacking in many of them .The proposed system overcomes all these problems . It uses RSA for the pre authentication and AES algorithm to to perform pre authentication.